Relative contribution of multi-source water recharge to riparian wetlands along the lower Yellow River. (1st November 2022) - Hong, Zhendong; Ding, Shengyan; Zhao, Qinghe; Geng, Zihan; Qiu, Pengwei; Zhang, Jian; Wang, An; Zhang, Panpan
Abstract: Rivers play a vital role in both the formation and maintenance of riparian wetland hydrology. However, few studies have focused on the response of water recharge of riparian wetlands to altered hydrological processes induced by water-sediment regulation practices. To fill this gap, our study investigated the contribution of multi-source water recharge of riparian wetlands in the lower Yellow River, as well as its influence both during and before the water-sediment regulation scheme of Xiaolangdi Dam. Our study is based on hydrochemistry and isotopic methods, using a Bayesian mixing model and artificial neutral network model. The results showed that riparian wetlands were fed by mixed sources, including groundwater, canals, the Yellow River, and precipitation. However, seasonal evaporation introduced additional variation, which affected the relative contribution of these sources across seasons. Among these sources, the Yellow River served as the main water source for recharging riparian wetlands, and its contribution varied both spatially and temporally (across seasons). Specifically, proximity of riparian wetlands was the primary factor explaining spatial variation in the contribution of Yellow River, while climatic (12.38%) and hydrological variabilities (87.62%) explained seasonal variation. Among these climatic and hydrological variables, suspended sediment content was the most important factor—with a relative contribution of 36.33%. By determining the contribution of the Yellow River to the recharge of riparian wetlands, our study has provided information which is beneficial to adaptive management of river-fed riparian wetlands, especially under the implementation of water-sediment regulation practices. Graphical abstract: Image 1 Highlights: The contribution of multi-source water recharge of riparian wetlands was quantified. The Yellow River was the main water source recharging riparian wetlands besides rainfall water. The contribution of the Yellow River inside the dykes was always larger. The effect of hydrological variation was considerably greater than that of climate variation. The change in suspended sediment content of the Yellow River was the most dominant driving factor.